Carbohydrate intake quality and gestational diabetes mellitus, and the modifying effect of air pollution - Zhang, Hehua; Xia, Yang; Zhang, Xiangsu; Chang, Qing; Zhao, Yuhong (Frontiers in Nutrition, 2023)
Background: Nutritional management is the cornerstone of gestational diabetes mellitus (GDM) prevention. High quality instead of low quantity of carbohydrate intake has been paying attention in controlling glycemia. Air pollution exposure can be interacted with dietary sourced nutrients, which may modify the associations with GDM. This study aims to explore the associations between overall quality of carbohydrate intake and GDM as well as the modifying effect of prenatal air pollution exposure. Methods: Carbohydrate quality index (CQI) was calculated was calculated by summing scores of the four components; Land use regression prediction models were used to assess the air pollution exposure levels. GDM definition was based on 75g glucose tolerance test results. Associations between pre-pregnancy CQI, pre-natal air pollution as well as the modifying effect on GDM were explored based on a birth cohort in China. Results: 3183 participants were included, of which 784 (24.63%) were diagnosed with GDM. Higher pre-pregnancy CQI was associated with a lower incidence of GDM (odds ratio [OR] = 0.75, 95% confidence interval [CI]: 0.56–0.99, P for trend = 0.04), especially for higher fasting blood glucose related GDM (OR = 0.66, 95%CI: 0.47, 0.91). Higher air pollution exposure before and during pregnancy was associated with a greater risk of GDM. Higher exposure to particulate matter with an aerodynamic diameter of < 2.5 μm (P for interaction < 0.01), particulate matter with an aerodynamic diameter of < 10 μm (P for interaction < 0.01), and sulfur dioxide (P for interaction = 0.02) during pregnancy decreased the beneficial effect of high pre-pregnancy CQI on GDM. Conclusions: CQI related dietary interventions pre-pregnancy to prevent GDM incidence should be considered. Women who are planning to be pregnant should avoid high exposure to air pollution during pregnancy.